2022
DOI: 10.3390/ijerph192315491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resistance Training on the Rehabilitation of Elderly Patients with Sarcopenia: A Meta-Analysis

Abstract: Resistance training is considered to be an efficient treatment for age-related sarcopenia and can improve muscle strength and quality in patients. However, there are currently no recommendations on resistance training parameters to improve muscle strength and quality in elderly patients with sarcopenia. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) and included 13 eligible RCTs. Resistance training significantly improved grip strength, gait speed, and skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
1
22
2
1
Order By: Relevance
“…Future research is needed to test interventional strategies focusing on all these factors to evaluate improvement in muscle quality and quantity. Given that resistance exercise induces significant changes in the expression of 26 genes (out of 73 implicated genes) in human skeletal muscle compared to the pre-training state, our findings also partly explain beneficial effects of strength training in the prevention and treatment of sarcopenia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future research is needed to test interventional strategies focusing on all these factors to evaluate improvement in muscle quality and quantity. Given that resistance exercise induces significant changes in the expression of 26 genes (out of 73 implicated genes) in human skeletal muscle compared to the pre-training state, our findings also partly explain beneficial effects of strength training in the prevention and treatment of sarcopenia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports experts’ opinion that physical activity should be the first-line therapy to counteract age-related sarcopenia [ 51 , 52 , 53 , 54 ]. Numerous studies have reported that different exercise training modalities might improve upper- and lower-limb muscle strength in older adults [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Specific attention has been paid to resistance training-type exercise [ 62 ], since exercise aspects may be safely and easily adjusted to stimulate type II muscle fibers and produce significant improvements in muscle strength [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic review and meta-analysis studies have revealed the efficacy of RET in helping older adults with sarcopenia successfully recover WS, with an overall effect size of 1.50–2.01 on WS recovery [ 41 , 79 ]. In the present study, on older patients with KOA who had sarcopenia, the RET group had a higher probability of WS recovery (adjusted HR = 2.21) compared with the UC group, with an estimated effect size of 0.62 on time to recover a normal WS [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%